Non-Mammalian Vertebrates: Distinct Models to Assess the Role of Ion Gradients in Energy Expenditure - Geisler, Caroline E.; Kentch, Kyle P.; Renquist, Benjamin J. (Frontiers in Endocrinology, 2017)
Animals store metabolic energy as electrochemical gradients. At least 50% of mammalian energy expenditure is used to maintain electrochemical gradients across the inner mitochondrial membrane (H+), the sarcoplasmic reticulum (Ca++), and the plasma membrane (Na+/K+). The potential energy of these gradients can be used to perform work (e.g. transport molecules, stimulate contraction, release hormones) or can be released as heat. Because ectothermic species adapt their body temperature to the environment, they are not constrained by energetic demands that are required to maintain a constant body temperature. In fact, ectothermic species expend 7-8 times less energy than similarly sized homeotherms. Accordingly, ectotherms adopt low metabolic rates to survive cold, hypoxia, and extreme bouts of fasting that would result in energy wasting, lactic acidosis and apoptosis, or starvation in homeotherms, respectively. Ectotherms have also evolved unique applications of ion gradients to allow for localized endothermy. Endothermic avian species, which lack brown adipose tissue, have been integral in assessing the role of H+ and Ca++ cycling in skeletal muscle thermogenesis. Accordingly, the diversity of non-mammalian vertebrate species allows them to serve as unique models to better understand the role of ion gradients in heat production, metabolic flux, and adaptation to stressors including obesity, starvation, cold, and hypoxia.